“It's Sweet Without Condom”: Understanding Risky Sexual Behaviour Among Nigerian Female University Students - Anthony Idowu Ajayi; Ezebunwa E. Nwokocha; Oladele Vincent Adeniyi; Daniel Ter Goon (Online Journal of Health & Allied Sciences, 2018)
Background: Over a million people globally acquire sexually transmitted infections (STI) every day mainly through unprotected sexual contact. While the consequences of risky sexual behaviour are well documented, the literature on young educated women's perceptions of, and narratives about risky sexual behaviour is limited, and thus, it is difficult to fathom from available sources why such behaviour persists. This study examined the prevalence of sexual risk-taking and assessed female University students' knowledge of the consequences of unprotected sex and reasons why such behaviour persists. Paradoxes between their narratives and risky sexual behaviour were discussed. Methods: The study adopted a mixed study design involving a survey of 420 students selected using cluster random sampling, 20 in-depth interviews and 5 focus group discussions. The analysis of the quantitative data involves the use of descriptive and inferential statistics, while thematic content analysis was used to analyse the qualitative data. Results: High prevalence of unprotected sexual intercourse was reported and was not associated with age, year of study, place of residence and religion. The narratives of participants indicate that female university students were aware of the risks associated with unprotected sex. Participants generally condemned sexual risk-taking and asserted that freedom, peer influence, poverty, ignorance, lack of sex education, civilisation, promiscuity, and satisfying sexual urge were the reasons for the persistent risky sexual behaviour among female university students. Also, perceived reduced fun associated with condom use, nourishment of marital expectations, and equivalence of unprotected sex with trust are among the reasons for persistent sexual risk-taking among female university students. Conclusion: Our findings show that female students practice risky sexual behaviour despite having knowledge of its consequences. Change in sexual behaviour of this cohort will require multi-faceted strategies targeting socio-cultural norms and empowerment of women to develop skills in negotiating safe sex.